ANTIOXIDANT ACTIVITY AND TOXICITY EFFECT OF ELEVEN TYPES OF BARK EXTRACTS ACQUIRED FROM EUPHORBIACEAE - Saefudin Saefudin; Efrida Basri; Agus Sukito (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2018)
The use of natural antioxidants for medicinal purposes deserves thorough attention for their efficacy and possibly adverse toxicity. This paper studies the antioxidant actions and toxicity effects of bark extracts. The study focuses on eleven tree species of Euphorbiaceae family. Initially, bark samples from those trees were extracted using ethanol. The acquired extracts were examined for peroxide values with iodometric method. The bark extracts were chemically screened for possible antioxidant-compound contents, i.e. polyphenols, flavonoids, and saponins; and followed by oxidation-reduction test to assess the extract ability in vitro to scavenge free radicals in their standard sources, i.e. 2,2-diphenyl-1-picrylhydrazyl; altogether to determine qualitatively which species origin from bark extracts afforded the most potential as antioxidants. Toxicity test was performed on those bark extracts to assess their safety on living creatures, particularly humans as tried on shrimp larvae by counting their death, using the Brine Shrimp Lethality Test method. Results show that bark extracts of four plant species, i.e. Acalypha hispida Blume, Bischofia javanica Blume, Glochidion arboreum Blume and Sapium baccatum Roxb species afforded potentiality as antioxidants, because its peroxide value (POV) was lower than or somewhat above those of the positive control vitamin E (POV 89.45 μg/ml). However, bark extracts from Euphorbia antiquorum L, Euphorbia hirta L, and Jatropha podagrica Hook (i.e. LC50 : 238.85; 228.11 & 194.51 μg/ml) were highly toxic, because their LC50’s value< 1000 μg/ml.